2021
DOI: 10.1155/2021/9880309
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Anxiety, and Depression among Medical Undergraduate Students and Their Coping Strategies

Abstract: Background. Students’ mental health deteriorates after they enter medical school and continues to deteriorate throughout their training. Every individual has a certain number of coping resources, and once these coping resources are challenged, mental illness usually results. Objective. We aimed to determine the prevalence and severity of depression, anxiety, and stress as well as coping strategies used by medical undergraduate students enrolled in Arsi University. Methods. Institution-based, cross-sectional de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
2
10
1
2
Order By: Relevance
“…About the coping strategies, our study supports evidence from a previous observation related to medical students with depression, anxiety, and stress using more avoidance strategies during the pandemic 35 . Additionally, a prior study with Chinese medical students showed that depression and anxiety negatively correlated with positive coping and positively correlated with negative coping 51 .…”
Section: Interpretation Of Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…About the coping strategies, our study supports evidence from a previous observation related to medical students with depression, anxiety, and stress using more avoidance strategies during the pandemic 35 . Additionally, a prior study with Chinese medical students showed that depression and anxiety negatively correlated with positive coping and positively correlated with negative coping 51 .…”
Section: Interpretation Of Resultssupporting
confidence: 88%
“…Compared with previous studies about mental health problems among medical students in Brazil 2,33 , and with other studies during the COVID-19 pandemic [34][35][36] , the medical students who participated in our study show higher prevalence of depression, anxiety, and stress symptoms. The pandemic context seems to contribute to an increase in the overall prevalence of depression and anxiety in undergraduate medical students 10 .…”
Section: Interpretation Of Resultscontrasting
confidence: 71%
“…Firstly, over the past decades, disturbing trends toward global increase in prevalence of depression, anxiety, stress, [13,24] burnout, substance abuse as well as suicidal ideations in doctors and medical students in comparison to their peer groups and general population have been consistently reported. [14] Second, more and more studies are recently reporting development of symptoms of psychological distress quite early among budding doctors during their formative years in medical institutes. [12,13] This, in turn, poses hindrance in their academic capabilities during student life and can have deleterious effects in their clinical acumen in future.…”
Section: Discusssionmentioning
confidence: 99%
“…Consistent with prior studies, our correlational analysis data illustrated the beneficial effect of TEI on PH of medical students. [13,14] Negative association seen between global TEIQue-sf and DASS-21 scores indicates that students who possessed higher TEI skills experienced fewer symptoms of stress, anxiety and depression and were psychologically healthier as compared to their counterparts with lower TEI. Moreover, results of regression analysis revealed that TEI explained a statistically significant portion of variance in DASS-21 scores not explained by socio-demographics and educational dimensions.…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation